Relationships between running performance and the cross-sectional area of the psoas major, and peak oxygen uptake in elite junior long-distance runners - Yamanaka, R.; Matsubayashi, T.; Saeki, T.; Enomoto, Y.; Yamazaki, K.; Sugita, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2016)
The purpose of this study was to examine the relationships between running performance and the cross-sectional area of the psoas major, peak oxygen uptake, and running economy in male junior long-distance runners. The subjects were 37 male junior athletes who achieved good records in interscholastic athletic competition during 5 years (2011-2015). Their seasonal best times in a 5,000 m race (5,000m-SB) were 14:04.11 ± 0:07.25 (13:53.64-14:16.15). In a multiple regression analysis, 5,000m-SB was statistical significantly correlated with the cross-sectional area of psoas major (16.0 ± 1.7 cm2) measured on magnetic resonance imaging and peak oxygen uptake (4.25 ± 0.36 l min-1 [76.9 ± 5.8 ml min-1 kg-1]) during a lactate curve test comprising five stages. However, 5,000m-SB was not related to oxygen uptake at the work-load which was less than the load at the lactate threshold estimated by using the lactate curve test results. These results suggest that a high volume of the psoas major, the largest hip-flexor muscle, and peak oxygen uptake are among the important factors for junior long-distance runner performance.